Post-vaccination Monitoring to Assess Foot-and-Mouth Disease Immunity at Population Level in Korea - Park, Mi-Young; Han, You Jin; Choi, Eun-Jin; Kim, HeeYeon; Pervin, Rokeya; Shin, Wonseok; Kwon, Doheon; Kim, Jae Myoung; Pyo, Hyun Mi (Frontiers in Veterinary Science, 2021)
In South Korea, domestic cattle, pigs, and goats were subjected to mandatory foot-and-mouth disease (FMD) vaccination and year-round serosurveillance since 2011. In 2020, approximately USD 95 million was spent solely for FMD vaccine purchase for 59 million livestock, and 1.25 million samples were tested to estimate the population immunity and demonstrate the absence of virus circulation. As the FMD vaccination program was revised in 2018, the post-vaccination monitoring (PVM) was designed to evaluate the effectiveness of the vaccine program of three vaccines approved for routine use. To this end, monitoring post-vaccination immunity has been conducted by collecting 35,626 serum samples at 28 days post-vaccination following regular national vaccinations, which were carried out in April and in October in 2020. The design of the serological test for PVM was specially targeted at particular livestock groups, including dairy cattle, goats, and beef cattle aged 6–12 months, which were generally estimated to have a low expected seroprevalence. The risk factors had also been identified, considering the increased likelihood of infection in a particular location, herd size, and husbandry system applied in a targeted sample collection. Serum sample collection and SP-O and NSP antibody tests were performed by local veterinary laboratories using commercially available ELISAs. The current FMD vaccination program, which was performed twice a year following the regimen of primary vaccination and boost, resulted in over 80% population immunity. The seroprevalence monitored after the vaccination in fall was higher than the one studied in spring except in pigs. It was demonstrated that the seroprevalence of risk-based targeted samples ranged from 93.8 to 100% in cattle, 63.2 to 100% in pigs, and 20.0 to 100% in goats. Of note is the area near the North Korean borders which showed a relatively low seroprevalence among the targeted regions, and no NSP sero-positive reactor was detected in this region. When subpopulation immunity at the individual level was assessed, the seroprevalence in young cattle stock was slightly lower (95.8%) than that of adults (98.4%). In conclusion, the FMD vaccination campaign has been successfully implemented in Korea, and the PVM can be a supplementary program for massive routine surveillance in terms of providing timely information needed both to estimate population immunity and to properly target “risk-based surveillance.”